CONSUMERSâ PREFERENCE ON TRANSPORTATION MODE FOR SHORT DISTANCE TRAVEL - Atria, Neshya
As the demand of mobilization increases, people invent new transportation mode which is called online transportation. Nowadays, a lot of companies from different industries use loyalty program in their effort to maintain a relationship with customers and increase customer loyalty. Loyalty program is proved can increased customer loyalty. However it is still debatable, which kind of method that has strong effect to loyalty program. Thus, the objective of this research are to find out which factor that affects consumers’ decision to choose short distance transportation mode, which kind of loyalty program method that is preferable to customers, and which transportation mode that is preferable for short distance travel. The research using quantitative approach with the collection method of questionnaire which has distributed to 400 respondents. We design the stated preference questionnaire with eight alternative modes: online transportation car A, online transportation car B, private car, mini bus, bike online transportation A, bike online transportation B, private bike, and motor taxi using d-efficient design using NGENE software. The attributes for those alternatives are travel time, travel cost, walking time, loyalty program A, and loyalty program B. The research results show that there is an effect of loyalty program method towards consumers short distance travel choice. In addition, the most influence attributes are travel time and travel cost among all attributes.